2012
DOI: 10.1029/2011jd016909
|View full text |Cite
|
Sign up to set email alerts
|

Single scattering albedo of fine mineral dust aerosols controlled by iron concentration

Abstract: [1] Sign and magnitude of solar aerosol direct radiative forcing are largely determined by the aerosol single scattering albedo (SSA) and the albedo of the underlying scene (e.g., surface albedo). On a global scale, mineral dust aerosol has the largest mass emission rate, average column mass burden, and average optical depth of all aerosol types. Therefore, better understanding of its optical properties with a focus on SSA is of great importance. Here, we entrain ten bulk soil samples from deserts and semi-ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(127 citation statements)
references
References 64 publications
9
114
0
1
Order By: Relevance
“…Our results extend earlier research on the occurrences of iron-bearing minerals in Bodélé surface sediments and elsewhere in North Africa that aimed to establish linkages between dust mineralogy and potential environmental effects of dust (Lafon et al, , 2006Alfaro et al, 2004;Moreno et al, 2006;Mounkaila, 2006;Journet et al, 2008Journet et al, , 2104Chudnovsky et al, 2009;Lázaro et al, 2011;Maher, 2011;Shi et al, 2011;Moosmüller et al, 2012;Adetunji, 2014;Formenti et al 2014 a, b). These studies employed many methods for dust and soil mineralogy, including magnetic analyses, X-ray absorption analysis, X-ray diffraction, microscopy, elemental and isotopic chemistry combined with leaching experiments, as well spectroscopic techniques in the laboratory and applied to satellite retrievals.…”
Section: Implications For Radiative Properties and Fe Bioavailabilitysupporting
confidence: 76%
“…Our results extend earlier research on the occurrences of iron-bearing minerals in Bodélé surface sediments and elsewhere in North Africa that aimed to establish linkages between dust mineralogy and potential environmental effects of dust (Lafon et al, , 2006Alfaro et al, 2004;Moreno et al, 2006;Mounkaila, 2006;Journet et al, 2008Journet et al, , 2104Chudnovsky et al, 2009;Lázaro et al, 2011;Maher, 2011;Shi et al, 2011;Moosmüller et al, 2012;Adetunji, 2014;Formenti et al 2014 a, b). These studies employed many methods for dust and soil mineralogy, including magnetic analyses, X-ray absorption analysis, X-ray diffraction, microscopy, elemental and isotopic chemistry combined with leaching experiments, as well spectroscopic techniques in the laboratory and applied to satellite retrievals.…”
Section: Implications For Radiative Properties and Fe Bioavailabilitysupporting
confidence: 76%
“…Contrary to the MAE values, there is no statistically significant size dependence of the AAE values, ranging from 2.5 (±0.2) to 4.1 (±0.3), with an average of 3.3 (±0.7), for the PM 10.6 size fraction and between 2.6 (±0.2) and 5.1 (±0.4), with an average of 3.5 (±0.8), for the PM 2.5 fraction. Our values are in the range of those published in the literature (Fialho et al, 2005;Linke et al, 2006;Müller et al, 2009;Petzold et al, 2009;Yang et al, 2009;Weinzierl et al, 2011;Moosmüller et al, 2012;Denjean et al, 2016b), shown in Table 5. AAE values close to 1.0 are found for urban aerosols where fossil fuel combustion is dominant, while AAE values for brown carbon from incomplete combustion are in the range of 3.5-4.2 (Yang et al, 2009;Chen et al, 2015;Massabò et al, 2016).…”
Section: Spectral and Size Variability Of The Mass Absorption Efficiencysupporting
confidence: 75%
“…Balkanski et al (2007) showed that lowering the dust absorption properties to an extent that reconciles them both with the remote-sensing observations and the state of knowledge of the mineralogical composition allowed calculating the clear-sky shortwave radiative effect of dust in agreement with satellite-based observations. A significant number of observations have quantified the shortwave lightabsorbing properties of mineral dust both by direct measurements Linke et al, 2006;Osborne et al, 2008;McConnell et al, 2008;Derimian et al, 2008;Yang et al, 2009;Müller et al, 2009;Petzold et al, 2009;Moosmüller et al, 2012;Wagner et al, 2012;Ryder al., 2013a;Utry et al, 2014;Denjean et al, 2016a, b) and indirectly by quantifying the amount and the speciation of the light-absorbing compounds in mineral dust, principally iron oxides (Lafon et al, , 2006Lazaro et al, 2008;Derimian et al, 2008;Zhang et al, 2008;Kandler et al, 2007Kandler et al, , 2009Kandler et al, , 2011Formenti et al, 2014a, b).…”
Section: Introductionmentioning
confidence: 99%
“…This is a good approximation for samples dominated by BC, where AAE = ~1. However, for many aerosols, such as those from smoldering combustion, this simple relationship is not followed and AAE varies with wavelength (Moosmüller et al, 2012). Interpolations between the seven wavelengths can be used to infer more complex functions of wavelength for different sources, a fraction of which can be verified by the more detailed spectrometric analyses outlined above.…”
Section: Potential Uses Of Multiwavelength R and T Datamentioning
confidence: 99%